2016
DOI: 10.1007/s11694-016-9341-0
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of coriander (Coriandrum sativum L.) essential oil in tomato sauce

Abstract: Essential oils (EOs) of coriander were analyzed by gas chromatography-mass spectrometry. Linalool (73.05 %), a-pinene (9.18 %), gamma-terpinene (7.65 %), geranyl acetate (2.71 %), were the main components of coriander essential oil. The minimum inhibitory concentration (MIC) of coriander was 2700 ppm in broth macrodilution. 3 9 10 5 CFU/g Byssochlamys fulva was inoculated in tomato sauce and different concentrations of EOs were added to each sample. Sodium benzoate at MIC concentration (250 ppm) was added to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…For example, in CEO obtained from C. sativum seeds cultivated in Cuba, the content of linalool reached 54.56%, while the seeds from Brazil contained 77.48% linalool [22]. The group of Zamindar et al, 2016, found linalool (73.05%) as the main chemical compound in CEO, followed by α-pinene (9.18%), γ-terpinene (7.65%), and geranyl acetate (2.71%) [23]. In a study published by Momin et al, 2012, the major component of CEO was linalool (60–70%), followed by α-pinene, limonene, γ-terpinene, p -cymene, borneol, citronellol, camphor, geraniol, and geraniol acetate [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in CEO obtained from C. sativum seeds cultivated in Cuba, the content of linalool reached 54.56%, while the seeds from Brazil contained 77.48% linalool [22]. The group of Zamindar et al, 2016, found linalool (73.05%) as the main chemical compound in CEO, followed by α-pinene (9.18%), γ-terpinene (7.65%), and geranyl acetate (2.71%) [23]. In a study published by Momin et al, 2012, the major component of CEO was linalool (60–70%), followed by α-pinene, limonene, γ-terpinene, p -cymene, borneol, citronellol, camphor, geraniol, and geraniol acetate [24].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the samples fumigated with CEO alone or combined with SEO in the CS1 and CS2 mixtures, and also in the control sample, the appearance of Aspergillus, Mucor , and Cladosporium can be noticed. Promising results regarding the use of CEOs in mixtures has proven antifungal protection by mixing 800 ppm CEO with 250 ppm Cinnamomum cassia , from the Lauraceae family against Byssochlamys fulva [23]. In the case of the CS3 mixture, a minimal fungus load with Fusarium sp.…”
Section: Resultsmentioning
confidence: 99%
“…In previous papers regarding the antifungal and antimycotoxicogenic potential of individual EOs of coriander, thyme, and oregano, it was highlighted the contribution of thymol and o-cymene as the major components in thyme EO, linalool in coriander EO, and carvacrol and o-cymene in oregano EO [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Other minor compounds, such as caryophyllene, β-myrcene, p -cymene, and γ-terpinene, were identified in the three analysed EOs [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The essential oil of coriander had an inhibitory effect on Aspergillus flavus ( Lasram et al., 2019 ), and Leucoagaricus gongylophorus ( Morais et al., 2015 ). Besides, it demonstrated antimicrobial properties for food preservation ( Zamindar et al., 2016 ; El-Sayed et al., 2022 ), while the anti-yeast effect of the black seed extract was observed ( Nadaf et al., 2015 ). Although there are studies on the effectiveness of coriander, peppermint, and black seed extracts in vitro against fungal pathogens, only a few studies on Botrytis cinerea under in vitro conditions could be found ( Mohammadi et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%